A new composite solid electrolyte PEO/Li10GeP2S12/SN for all-solid-state lithium battery. (20th August 2016) - Chen, Bo; Huang, Zhen; Chen, Xiaotian; Zhao, Yanran; Xu, Qiang; Long, Peng; Chen, Shaojie; Xu, Xiaoxiong
Abstract: A new solid polymer electrolyte (SPE) PEO-LiTFSI-1%LGPS-10%SN is successfully prepared via a convenient method with low cost. The effect of SN on the ionic conductivity of PEO-based electrolyte is systematically investigated. It presents a maximum conductivity of 9.10 × 10 −5 S·cm −1 at 25 °C, and a 15-fold ion conductivity enhancement in PEO-LiTFSI. It exhibits wide electrochemical window (0–5.5 V) and excellent compatibility with metallic Li. The LiFePO4 /Li batteries exhibit a good cycling and rate performance under 40 °C, whose maximum discharge specific capacity at 0.1 C is 160.6 mAh·g −1, and 94.7% can be retained after 60 cycles. At 0.5C, the maximum discharge specific capacity is 138.4 mAh·g −1, and capacity retention close to 90% even after 100 cycles. The reasons of activation process are discussed. This new SPE with outstanding electrochemical performance is a promising solid electrolyte candidate for applications in all-solid-state lithium battery.